Redescription of three species of Filistatidae (Araneae) described by C.F. Roewer from Afghanistan - Zonstein, Sergei L.; Marusik, Yuri M.; Koponen, Seppo (Zootaxa, 2013)
Types of three filistatid species described by Roewer (1960, 1962) from Afghanistan are redescribed and two of them transferred to other filistatid genera. The new combinations proposed are: Zaitunia afghana (Roewer 1962) comb. n. (ex. Filistata Latreille, 1810) and Tricalamus lindbergi (Roewer, 1962) comb. n. (ex. Pritha Lehtinen, 1967). The taxonomic position of Pholcoides afghana Roewer, 1960 is discussed and the species is placed in the filistatid subfamily Prithinae Gray, 1994.